IBM 4331-PC XT link file transfer system - Tan, Arlene L. (Animo Repository, 1991)
The IBM 4331-PC/XT Link is a file transfer system which allows an ordinary IBM PC/XT compatible computer and an IBM 4331 mainframe to exchange files. The rationale for exchanging of files is to allow other users to be productive when the IBM 4331 system is being fully utilized. One way the users could be productive is to encode and debug their programs on a PC/XT and later upload the program to the IBM 4331 mainframe computer. In addition, the users could download their programs and make some revision with it in their own convenience. This is basically what the file transfer system is trying to accomplish. Listed within this thesis is a description on how the file transfer system between an IBM PC/XT and an IBM 4331 mainframe was accomplished. Specifically, it shows the description on how the hardware and the software works and interact with each other in order to make this system function.